Accounting for disasters: Evidence of under-representation of victims in the accountability process. Issue 3 (19th June 2019) - Agyenim-Boateng, Cletus; Oduro-Boateng, Kofi
Abstract : Purpose: The purpose of this paper is to investigate disaster accountability process, and it seeks to advocate for involvement of victims as salient stakeholders in the accountability process. Design/methodology/approach: The authors adopt a case study of the 3rd June, 2015 flood disaster and fire that occurred in Accra, Ghana and draw mainly on interviews, as well as observations and a review of publicly available documents. Findings: Several actors are involved in disaster management in Ghana. These actors play several roles as part of the disaster management process. Coordination is observed among some governmental actors. However, there is a little collaboration among these actors. There are, therefore, no clear accountability relationships between the actors. Moreover, the forms of accountability process are largely upward and internal. So, although we find the victims as salient stakeholders, their perspectives are not prioritised as part of the accountability process. Research limitations/implications: As a result of less engagement with victims in the accountability process, a central accountability concern, outcomes, namely, benefits for victims in terms of changes in their knowledge, status, attitudes, values, skills, behaviours or conditions were not promoted. Downward accountability should be encouraged to promote better outcomes. Originality/value: Although some studies on accounting for disasters have been undertaken, there is none in our local context, and also this study has been able to uncover under-representation of victims in the accountability process using adaptive accountability lens.